“Brighamia insignis” an Hawaiian Endangered Species, Current Status and Future Prospects: A Review: Brighamia insignis” an Hawaiian Endangered Species - Munawar, Tayyaba; Anwar, Khurshid; Bibi, Yamin; Ahmad, Farooq (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Plants are serving human beings through various aspects of life. But these natural servers are not out of danger. They are facing high alerts for the red zone category. This review is highlighting the critically endangered Hawaiian plant species Brighamia insignis belonging to the family Campanulaceae. Here is also a discussion about some of the threats to Brighamia insignis and its conservation methods to prevent it from extinction.